2002
DOI: 10.1260/135101002320941468
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Comparison of the Sound Insulation of Lightweight Partitions with Different Sound Absorbing Infills

Abstract: Measurements of sound reduction indices for lightweight gypsum board partitions filled with three different sound absorbing materials (rockwool, glasswool and polyurethane foam) are reported. For partitions where the gypsum panels are mounted on a common stud, with the sound absorbing infill in direct contact with both panels and for uncoupled double partitions, measurement results show that polyurethane foam, of high flow resistivity and stiffness, is less effective as an infill than either rockwool or glassw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Most of the studies in the literature are focussing on the construction of these materials that usually comprise one or more layers board on each side [1]- [4]. To improve the sound insulation, the installation of sound absorbing materials in the partition cavity was studied [2]. Presently, many researches are being conducted from the viewpoint of constructing the structural design within a building walls, but few have paid attention to enhance the TL by incorporating smart materials.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies in the literature are focussing on the construction of these materials that usually comprise one or more layers board on each side [1]- [4]. To improve the sound insulation, the installation of sound absorbing materials in the partition cavity was studied [2]. Presently, many researches are being conducted from the viewpoint of constructing the structural design within a building walls, but few have paid attention to enhance the TL by incorporating smart materials.…”
Section: Introductionmentioning
confidence: 99%
“…Bravo et al17 2002Performed measurements of SRI for lightweight gypsum board partitions filled with different sound absorbing materials such as Rockwool, polyurethane, and glass wool. It was found that the SRI for the three sound absorbing materials is the same at below 630 Hz, but above this frequency, polyurethane gives lower SRI possible due to its lower absorption coefficient than that of Rockwool and glass wool Sugie et al18 2014Studied the improvement of sound insulation of lightweight double-leaf partition at low frequencies by using several fibrous absorbers with different bulk densities and thicknesses.…”
mentioning
confidence: 99%